A reliability evaluation method based on the weakest failure modes for side-by-side offloading mooring system of FPSO. (May 2016) - Zhang, Xu; Sun, Liping; Ma, Chunhui; Fassezke, Ethan; Sun, Hai
Abstract: Offshore structures are complex systems, and numerous failure modes must be taken into consideration when reliability analysis in different loads and environment conditions are conducted on them. It is difficult to obtain structural system reliability with respect to complicated systems with numerous failure modes and dependency consideration among them. This paper applies the combination of the weakest failure modes theory with structural reliability theory to conduct reliability analysis on of side-by-side offloading mooring system of FPSO. Firstly, the numerical simulation of the system in different conditions is addressed to acquire the statistical data of time-history stress of components including hawsers, fenders and yoke, based on which, the reliability indexes of all the failure modes and correlation coefficient matrix are derived. Then the weakest failure modes, i.e. the representative failure modes that have significant impact on the system, are located through Probability Network Evaluation Technique. The probability of structural system is estimated through the weakest failure modes by considering the system as series. The analysis results indicate that two environment conditions (0°&0°&0° and 0°&30°&45° in combinations of wave, wind and current) are relative dangerous, which is in good correspondence with the practical expertise. The method is verified to be an effective and convenient evaluation approach for structural reliability analysis in terms of complex systems. It is beneficial for the identification of structure indicators from the weakest failure mode group and conduct optimum of structural system configurations in the design stage. Highlights: This paper provides an effective approach for reliability calculation of a complex system and achieves the application of the method in the SBS offloading system. The efficiency for evaluation of reliability index of a complex system is largely promoted by the weakest failure modes theory. A real SBS offloading system is chosen as the simulation object which operates in South China Sea, which ensures authenticity of stress results.